Norovirus acute gastroenteritis amongst US and European travellers to areas of moderate to high risk of travellers’ diarrhoea: a prospective cohort study - Alberer, Martin; Moe, Christine L; Hatz, Christoph; Kling, Kerstin; Kirby, Amy E; Lindsay, Lisa; Nothdurft, Hans D; Riera-Montes, Margarita; Steffen, Robert; Verstraeten, Thomas; Wu, Henry M; DuPont, Herbert L (Journal of travel medicine, 2024)
Abstract Background Acute gastroenteritis (AGE) is a major medical condition for travellers worldwide, particularly travellers to low- and middle-income countries. Norovirus (NoV) is the most common cause of viral AGE in older children and adults, but data on prevalence and impact amongst travellers is limited. Methods Prospective, multi-site, observational cohort study conducted 2015–2017, amongst adult international travellers from the US and Europe to areas of moderate to high risk of travel-acquired AGE. Participants provided self-collected pre-travel stool samples and self-reported AGE symptoms whilst travelling. Post-travel stool samples were requested from symptomatic subjects and a sample of asymptomatic travellers within 14 days of return. Samples were tested for NoV by RT-qPCR, genotyped if positive and tested for other common enteric pathogens by Luminex xTAG GPP. Results Of the 1109 participants included, 437 (39.4%) developed AGE symptoms resulting in an overall AGE incidence of 24.7 per 100 person-weeks [95% confidence interval (CI): 22.4; 27.1]. In total, 20 NoV-positive AGE cases (5.2% of those tested) were identified at an incidence of 1.1 per 100 person-weeks (95% CI: 0.7; 1.7). NoV-positive samples belonged mostly to genogroup GII (18, 85.7%); None of the 13 samples sequenced belonged to genotype GII.4. Clinical severity of AGE was higher for NoV-positive than for NoV-negative cases (mean modified Vesikari Score 6.8 vs 4.9) with more cases classified as severe or moderate (25% vs 6.8%). In total, 80% of NoV-positive participants (vs 38.9% in NoV-negative) reported at least moderate impact on travel plans. Conclusions AGE is a prevalent disease amongst travellers with a small proportion associated with NoV. Post-travel stool sample collection timing might have influenced the low number of NoV cases detected; however, NoV infections resulted in high clinical severity and impact on travel plans. These results may contribute to targeted vaccine development and the design of future studies on NoV epidemiology.